Melangkah ke alaf baharu - Mahathir Mohamad Tun, 1925- (Siri ucapan presiden UMNO., 2005)
History and development of UMNO in Malaysian politics and government; collected speeches of Mahathir bin Mohamad, Prime Minister of Malaysia, 1981-2003.